A Rare Case of Antiphospholipid Syndrome in a 28-year-old Male with Discoid Lupus Erythematosus - Islam, Farzana; Rasel, Mohammad; Ghose, Susmita; Das, Sujan Kumar; Hossain, Mohammad Zaid; Rouf, Mostafa Kamal (Bangladesh Journal of Medicine, 2024)
Antiphospholipid syndrome (APS) is an autoimmune disorder characterized by thromboembolic events associated with antiphospholipid antibodies. While thrombosis is the most well-known pathogenic mechanism in this disorder, the relevance of some other mechanisms such as arterial stenosis is being increasingly recognized. The underlying patho-physiology of stenotic arterial vasculopathy is not fully understood but some recent studies revealed APS presenting with new insights into the molecular mechanism behind this endothelial cell activation in APS. We present a case of a 28-year-old male who presented with painful digital ischemia and generalized hyperpigmented papulo-necrotic cutaneous lesions. The presence of lupus anticoagulant (LA) antibody and skin biopsy consistent with DLE, confirmed the diagnosis of APS secondary to DLE. And the CT angiogram showed stenosis of radial and ulnar arteries and no evidence of thrombosis. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 179-180